A randomised controlled trial of occupational therapy for stroke patients not admitted to hospital - Walker, Marion Fraser (1999)
Not all stroke patients are admitted to hospital. The literature indicates that between 22% and 60% of stroke patients remain in the community, often with little or no rehabilitation.